REVISITING THE TRADITION IN T. S. ELIOT’S THE WASTE LAND - Bhat, Asif Gulzar; Hussain, Syed Muntaza; Lone, Junaid Rashid; Bhat, Shafaat Hussain (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Modern literature has been aligned with new principles, introducing innovative paradigms, and offering alternative perspectives. Iterations and repetitions became principal features of modern aesthetics. T. S. Eliot’s intertextual dialogue and allusions significantly echo previous works of art, cultures and traditions. This paper focuses on T. S. Eliot’s The Waste Land (1922), which exhibits a different stylistic approach. Rereading the poem with Derrida’s Iterability as analytical tool could aid in deciphering different meanings. This paper aims to analyse how language, scenes, characters, and allusions to different religions and philosophies are revisited from their intended context and used in a new style. They create retroactive meanings, make communication possible, and embody the perfect conditions of the time in which the poem was written. Derrida argues that iterability refers that the text’s communication could be possible without a recipient or contributor and allows a text to communicate beyond its intended context and audience.